2013
DOI: 10.1007/s00271-013-0409-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mulched drip irrigation for cotton in arid Northwest China

Abstract: Field experiments were conducted in arid Southern Xinjiang, Northwest China, for 3 years to evaluate sustainable irrigation regimes for cotton. The experiments involved mulched drip irrigation during the growing season and flood irrigation afterward. The drip irrigation experiments included control experiments, experiments with deficit irrigation during one crop growth stage, and alternative irrigation schemes in which freshwater was used during one growth stage and relatively saline water in the others. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 32 publications
0
75
0
Order By: Relevance
“…Southern Xinjiang had an average cotton yield over three years from 3.6 to 5.1 t·ha with a low EC in the top 30 cm soil from 3 to 11 dS·m −1 [43]. As research mentioned above, our WUE data were lower (0.53 kg·m ), except for WUE and IWUE data at Korla.…”
Section: Water Use Efficiency In Different Saline Soilsmentioning
confidence: 59%
“…Southern Xinjiang had an average cotton yield over three years from 3.6 to 5.1 t·ha with a low EC in the top 30 cm soil from 3 to 11 dS·m −1 [43]. As research mentioned above, our WUE data were lower (0.53 kg·m ), except for WUE and IWUE data at Korla.…”
Section: Water Use Efficiency In Different Saline Soilsmentioning
confidence: 59%
“…The distribution of soil solution salinity (EC sw ) was simulated as a non-reactive solute (Ramos et al, 2011;Phogat et al, 2012;Phogat et al, 2014;Wang et al, 2014). These studies demonstrated a good prediction of salinity under intensive irrigation and fertigation, similar to practices in the region under study.…”
Section: Soil Salinity Simulationmentioning
confidence: 76%
“…The threshold and slope model parameters were obtained from the previous regional study (Zhang et al, 2002) evaluating salinity thresholds (EC e = 2.1 dS/m) and percent reductions (12.8%) in different root stocks of grapevine. The temporal and spatial distribution of soil solution salinity (EC sw ) was modeled as a non-reactive solute (e.g., Ramos et al, 2011;Wang et al, 2014;Phogat et al, 2014). These studies demonstrated that this approach could be successfully used in environments under intensive irrigation and fertigation management.…”
Section: Model Descriptionmentioning
confidence: 99%